2017
DOI: 10.1111/bjh.15012
|View full text |Cite
|
Sign up to set email alerts
|

CD34+ selected stem cell boosts can improve poor graft function after paediatric allogeneic stem cell transplantation

Abstract: SummaryPoor graft function (PGF) is a severe complication of haematopoietic stem cell transplantation (HSCT) and administration of donor stem cell boosts (SCBs) represents a therapeutic option. We report 50 paediatric patients with PGF who received 61 boosts with CD34 + selected peripheral blood stem cells (PBSC) after transplantation from matched unrelated (n = 25) or mismatched related (n = 25) donors. Within 8 weeks, a significant increase in median neutrophil counts (0Á6 vs. 1Á516 9 10 9 /l, P < 0Á05) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 22 publications
3
31
0
Order By: Relevance
“…In the patients with PGF who had a hematopoietic response, the median CD34 + dose was higher than that in the patients who did not show a response. In a recent study, a CD34 + cell dose >3.25 £ 6 /kg was related to a better improvement in neutrophil count [12]; however, no multivariate analysis found a cutoff value of CD34 + cells correlated with hematopoietic recovery. We suspected that two aspects may affect the result.…”
Section: Discussionmentioning
confidence: 87%
“…In the patients with PGF who had a hematopoietic response, the median CD34 + dose was higher than that in the patients who did not show a response. In a recent study, a CD34 + cell dose >3.25 £ 6 /kg was related to a better improvement in neutrophil count [12]; however, no multivariate analysis found a cutoff value of CD34 + cells correlated with hematopoietic recovery. We suspected that two aspects may affect the result.…”
Section: Discussionmentioning
confidence: 87%
“…Another study focused mainly on pediatric patients ( n = 50) also identified good tolerance and efficacy. 70 To generate SCB, donors traditionally must undergo an additional peripheral blood stem-cell (PBSC) collection. However, realistically, many patients might not be able to receive fresh SCB if their donors are unwilling or unable to accept another PBSC collection.…”
Section: Treatmentsmentioning
confidence: 99%
“…One of the most significant parameters for improved OS was the increased number of CD34 + stem and progenitor cells produced by G‐CSF administration prior to donor lymphocyte collection. It is an established procedure to administer purified CD34 + cells after allo‐HCT in case of mixed chimerism or poor graft function (Chandra et al , ; Mainardi et al , ). Moreover, CD34 + stem cell dose is one of the most important parameters to evaluate graft quality and predict haematopoietic recovery in autologous‐ and allo‐HCT settings (Weaver et al , ; Allan et al , ; Torlen et al , ; Rezvani et al , ).…”
Section: Discussionmentioning
confidence: 99%